1984
DOI: 10.1007/bf00964526
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of crayfish glutamic acid decarboxylase

Abstract: Crayfish glutamic acid decarboxylase (GAD), like the homologous enzymes from other species, is inhibited by carbonyl-trapping agents (e.g. aminooxyacetic acid; AOAA) and sulfhydryl reagents (e.g. 5,5'-dithiobis-(2-nitrobenzoic acid); DTNB). It also is inhibited by the product GABA, many anions (e.g. SCN- and Cl-), and some cations (e.g. Zn+2). The inhibition by AOAA, but not that by DTNB, was prevented by increasing the concentration of the pyridoxal phosphate (PLP) coenzyme. GABA blocked the effects of PLP on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…NMRS analyses of cerebrum extracts showed that the reduced concentrations of GABA were caused by decreased neuronal synthesis of GABA from glucose, indicating that the process is affected by changes in the number of synaptic vesicles. The steady-state concentration of GABA in vivo is primarily regulated by GAD activity (Roberts and Simonsen 1963;Martin and Rimvall 1993;Battaglioli et al 2003), and previous studies have shown that increased cytosolic concentrations of GABA can down-regulate its own synthesis through feedback inhibition of GAD (Grossfeld et al 1984;Porter and Martin 1984;Rimvall and Martin 1994;Battaglioli et al 2003). The protein level of GAD (Rosahl et al 1995), and GAD activity measured at optimal conditions in vitro, were similar in cerebrum homogenates from synapsin DKO and wild-type mice (unpublished results).…”
Section: Discussionmentioning
confidence: 55%
“…NMRS analyses of cerebrum extracts showed that the reduced concentrations of GABA were caused by decreased neuronal synthesis of GABA from glucose, indicating that the process is affected by changes in the number of synaptic vesicles. The steady-state concentration of GABA in vivo is primarily regulated by GAD activity (Roberts and Simonsen 1963;Martin and Rimvall 1993;Battaglioli et al 2003), and previous studies have shown that increased cytosolic concentrations of GABA can down-regulate its own synthesis through feedback inhibition of GAD (Grossfeld et al 1984;Porter and Martin 1984;Rimvall and Martin 1994;Battaglioli et al 2003). The protein level of GAD (Rosahl et al 1995), and GAD activity measured at optimal conditions in vitro, were similar in cerebrum homogenates from synapsin DKO and wild-type mice (unpublished results).…”
Section: Discussionmentioning
confidence: 55%
“…To test this possibility, five different compounds, presumed to play a role as either a substrate analogue or an antagonist in the GDAR system, were selected. These include 3-mercaptopropionic acid, which is an analogue of glutamate, and the other four, including aminooxyacetic acid, 4-deoxypyridoxine hydrochloride, isoniazid, and thiosemicarbazide, are antagonists of pyridoxal phosphate, a cofactor of GadA and GadB [ 35 - 42 ]. The concentrations of tested compounds were determined by measuring the maximal concentrations with no growth inhibitory effects at pH 7.0: 3-mercaptopropionic acid at 0.5 mM, aminooxyacetic acid at 0.02 mM, 4-deoxypyridoxine hydrochloride at 1 mM, isoniazid at 1 mM, and thiosemicarbazide at 0.2 mM.…”
Section: Resultsmentioning
confidence: 99%
“…Besides glucose, glutamic acid is the only compound used for brain fuel. The brain converts glutamic acid to a compound that regulates brain cell activity (Grossfeld et al 1984). Glutamic acid increases the firing of neurons in the nervous system.…”
Section: Introductionmentioning
confidence: 99%